Enzymatic, immunological and phylogenetic characterization of Brucella suis urease - Contreras-Rodriguez, Araceli (BioMed Central, 2008)
BACKGROUND: The sequenced genomes of the Brucella spp. have two urease operons, ure-1 and ure-2, but there is evidence that only one is responsible for encoding an active urease. The present work describes the purification and the enzymatic and phylogenomic characterization of urease from Brucella suis strain 1330. Additionally, the urease reactivity of sera from patients diagnosed with brucellosis was examined. RESULTS: Urease encoded by the ure-1 operon of Brucella suis strain 1330 was purified to homogeneity using ion exchange and hydrophobic interaction chromatographies. The urease was purified 51-fold with a recovery of 12% of the enzyme activity and 0.24% of the total protein. The enzyme had an isoelectric point of 5, and showed optimal activity at pH 7.0 and 28–35°C. The purified enzyme exhibited a Michaelis-Menten saturation kinetics with a K(m )of 5.60 ± 0.69 mM. Hydroxyurea and thiourea are competitive inhibitors of the enzyme with K(i )of 1.04 ± 0.31 mM and 26.12 ± 2.30 mM, respectively. Acetohydroxamic acid also inhibits the enzyme in a competitive way. The molecular weight estimated for the native enzyme was between 130–135 kDa by gel filtration chromatography and 157 ± 7 kDa using 5–10% polyacrylamide gradient non-denaturing gel. Only three subunits in SDS-PAGE were identified: two small subunits of 14,000 Da and 15,500 Da, and a major subunit of 66,000 Da. The amino terminal sequence of the purified large subunit corresponded to the predicted amino acid sequence encoded by ureC1. The UreC1 subunit was recognized by sera from patients with acute and chronic brucellosis. By phylogenetic and cluster structure analyses, ureC1 was related to the ureC typically present in the Rhizobiales; in contrast, the ureC2 encoded in the ure-2 operon is more related to distant species. CONCLUSION: We have for the first time purified and characterized an active urease from B. suis. The enzyme was characterized at the kinetic, immunological and phylogenetic levels. Our results confirm that the active urease of B. suis is a product of ure-1 operon.